Analysis And Design Of Point Of Sale System In D'astore Shop - Rifandi, Ahmad (Aptisi Transactions On Technopreneurship (ATT), 2020)
Science and technology have experienced quite rapid development. with advances in science and technology that are all sophisticated and modern, computers are a very important means of their role to help humans in overcoming various work problems in companies, agencies or organizations. The purpose of this Job Training Report Writing is to do an analysis of the store d 'store. where currently the processing of buying and selling data is still manual. The method used is the method of data collection consisting of interview or interview methods, library methods, observation methods. And includes methods of analysis and design carried out using the Unified Modeling Language (UML) method. From the analysis and observations made, it can be seen that the recording and making of reports are still inadequate so as to make the decision process slow, the authors intend to design the Point of Sale System with the Unified Modeling Language (UML) method. The data used to process the design includes user data, item data, sales data, purchase data, supplier data, item type data, supplier type data, reports. The conclusion of this study shows that sales at the D’STORE SHOP requires a system that simplifies sales performance, saves time and is easy to run, so that better customer service increases and the data presentation process is more organized and runs well.